Efek Good Corporate Governance Dan Rasio Keuangan Terhadap Pengungkapan Enterprise Risk Management - Dewi Noviana; Agoestina Mappadang (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
The purpose of this study is to clarify how good corporate governance and financial ratios affect a company's risk management. Data and information on ERM, obtained from annual reports, management reports and annual corporate governance. The purposive examining method turned into applied in determining the take a look at gotten through 34 groups from fifty seven basis department groups recorded at the Indonesia Stock Exchange with six years of remark from 2015 to 2020, in order that 204 look at take a look at had been gotten. The findings of this look at found out that Good Corporate Governance, particularly the Independent Board of Commissioners, Audit Committee, Risk  Management Committee, and Leverage, had no giant effect at the Company`s Risk  Management, while Profitability had a giant high quality effect at the ranges of company threat control in infrastructure groups indexed at the Stock Exchange. Indonesian Securities for the 2015-2020 period. However, as a whole, the ERM chart for the 2015-2020 period, when companies participate in the Enterprise Risk Management Index, combines the presence of independent, audit and risk  Management committees, leverage and profitability factors. Affects the index. Measures infrastructure companies listed on the Indonesia Stock Exchange. Another result of this study is that the most common type of risk is financial risk.